, ; Bioenergie as a source of income of agricultural enterprises - Oksana Makarchuk; Heinrich Hockmann; Aleksej Lissitsa (Leibniz Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2007)
, , . , . - , , (). " " , - , - , . , - . . , . . . - , . – – Enterprise activity is based on maximization of profit to increase the volume of own capital, to expand manufacture and to guarantee the earning of profit for the long-term period. Therefore everyone searches for new sources of the income by means of which it is possible to maximize cost of the made product. One of new sources of the income in agriculture is a cultivation of agricultural crops for the energy, heat, fuel (biofuel) manufacture. In this discussion paper the market is examined for biofuel, as well as their competitiveness is analyzed in comparison to mineral fuels. Germany takes the lead positions on manufacture and use of biofuel among the countries of the European Union and Ukraine has a big potential on the agricultural commodities market and big possibilities of development for biofuel. The modern market of biofuel is characterized by the constant tendency to development and growth of manufacture. The supply and the demand at the market is strongly depends on the state energy policy. In the work it is also shown that the production of biofuel is not competitive without state support.
urn:nbn:de:gbv:3:2-5676
Keywords: Q12; Q27; 330; Biofuel; bioethanol; biomass; renewed energy sources; competitiveness; supply and demand